Party system change : approaches and interpretations - Mair, Peter (Clarendon Press ; Oxford University Press, 1997)
Mair examines how we interpret the evidence of change and stability in modern parties and party systems. Focusing on processes of political adaptation and control, he also looks at how parties generate or freeze their own momentum.